The influence of head impact threshold for reporting data in contact and collision sports: Systematic review and original data analysis - King, D.; Hume, P.; Gissane, C.; Brughelli, M.; Clark, T. (Sports Medicine, 2016)
Head impacts and resulting head accelerations cause concussive injuries. There is no standard for reporting head impact data in sports to enable comparison between studies.